PENERAPAN SISTEM TANAM LEGOWO PADA USAHA TANI PADI UNTUK MENINGKATKAN PRODUKSI DAN PENDAPATAN PETANI - Suparwoto, Suparwoto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2010)
Various efforts to increase rice productivity through technological breakthroughs that could improve the efficiency of rice farming. One of the alternative technologies of integrated crop management (ICM) is the application of rice cropping systems legowo. This paper is a review of some literature research and assessment of annual reports, and proseding . Based on the results of a review journal of the literature indicates that the application of ICM legowo rice cropping system provides several benefits including: increased production significantly for 25.7 to 26.9 percent and revenue of Rp. 1.480.000 - Rp. 2.121.500, - per hectare compared with the symmetric planting system (tegel) in lowland swamp land and irrigated land. This technology is economically quite profitable as indicated by the value of B / C ratio greater than one and deserves to be disseminated.